1988
DOI: 10.1159/000125081
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Factor: Evidence for a Neurotransmitter Role in the Locus ceruleus during Hemodynamic Stress

Abstract: Corticotropin-releasing factor (CRF) is localized in fibers in the noradrenergic nucleus locus ceruleus (LC) and alters LC discharge characteristics when administered centrally. To determine whether CRF functions as a neurotransmitter in the LC during stress, the effects of hemodynamic stress on LC discharge were compared to those of CRF. Hemodynamic stress elicited by intravenous nitroprusside infusion produced identical effects on LC spontaneous and sensory-evoked discharge as those reported for centrally ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0
2

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 0 publications
6
76
0
2
Order By: Relevance
“…Both electrophysiological and biochemical studies have shown that CRH increases the spontaneous discharge rate of LC neurons, increases norepinephrine release and increases tyrosine hydroxylase protein levels in the LC. 21,23,[50][51][52] Furthermore, depending on the type of stressor, the stress-induced activation of LC neurons appears to be mediated by CRH presumably released from terminals within the LC region. 21,22,53 These findings are consistent with the elevation in CRH levels in the LC following stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both electrophysiological and biochemical studies have shown that CRH increases the spontaneous discharge rate of LC neurons, increases norepinephrine release and increases tyrosine hydroxylase protein levels in the LC. 21,23,[50][51][52] Furthermore, depending on the type of stressor, the stress-induced activation of LC neurons appears to be mediated by CRH presumably released from terminals within the LC region. 21,22,53 These findings are consistent with the elevation in CRH levels in the LC following stress.…”
Section: Discussionmentioning
confidence: 99%
“…21,23,[50][51][52] Furthermore, depending on the type of stressor, the stress-induced activation of LC neurons appears to be mediated by CRH presumably released from terminals within the LC region. 21,22,53 These findings are consistent with the elevation in CRH levels in the LC following stress. 54 Recent studies have also provided evidence of a neurotransmitter role for CRH on serotonin neurons in the DR. For example, injection of CRH into the ventricles or directly into the DR of rats inhibited the discharge rate of serotonin neurons in the DR. 24,25 However, Lowry et al, 26 using an in vitro slice preparation, reported that CRH had no effect on the firing rate of serotonin neurons from control rats, but significantly increased the firing rate of serotonin neurons from rats previously exposed to repeated restraint stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitroprusside is known to increase the rate of discharge of LC noradrenergic neurons, presumably because of the consequent acute hypotension (32). A relationship between CRF and noradrenergic neurons may be functional during hypotension because &rfth d.p.…”
Section: Such Activation Also Occurs Following Icv Administration Of mentioning
confidence: 99%
“…These neurons project to the ME where they secrete CRH into the hypophyseal portal blood (19). These PVN neurons also project to various brainstem nuclei, such as the locus coeruleus, the parabrachial and vagal nuclei where CRH may be involved in modulating hemodynamic function and in coordination of stress responses (85). CRH neurons also are present in the amygdala and in the cerebral cortex, however, the function of CRH in these regions is currently unknown (78,79).…”
Section: Factors Influencing Anterior Pituitary Corticotropin Secretionmentioning
confidence: 99%